(untitled) (Medicine Today, 2024)
Introduction with Objective: The aim of the present study was to assess the fixation methods for metacarpal bone fracture. Materials and Methods: A prospective observational study was conducted from February 2019 to January 2020 among 29 metacarpal bone fracture patients attending at orthopedic surgery department, Chittagong Medical College Hospital, Chittagong after obtaining requisite consent from the patient. Data were collected through the assessment and X-ray report of patients in the orthopedic surgery Department. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the fixation methods for metacarpal bone fracture. Results: Most of the study population (89.7%) was in 18-40 years of age group. The mean age of the patients was 33.14 ± 11.895 years (range: 18-70 years). Service was the mostly occurring occupation among the patients (35%) and worker were 31%. In our study transverse fracture was 51.7% and oblique fracture was 41.4%. In case of method of fixation, maximum (65.5%) patient’s fixations were done by mini plate, 31% were by K-wire and 3.4% were by both K-wire & lag screw. In case of number of metacarpal bone involvement, 1 bone was involved in maximum (75.9%), 2 bone were involved in 17.2% and 3 bone were involved in 6.9% patients. Conclusion: Closed or minimally invasive fixation with K-wire, mini plates and screws are safe methods and can be performed with minimal complications. Maximum (65.5%) patient’s fixations were done by mini plate. Medicine Today 2024, Vol.36 (2): 87-89